Health and Economic Growth: Reconciling the Micro and Macro Evidence - Johannes Schünemann; David E. Bloom; David Canning; Rainer Kotschy; Klaus Prettner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
There are two prominent methods to assess the effects of health on economic growth. The first is based on the estimated returns on health by means of Mincer wage regressions that are aggregated to derive the macroeconomic effects of population health. The second approach is based on the estimation of a generalized aggregate production function that decomposes human capital into its different components, in particular, population health. While the overwhelming majority of studies based on both methods indicates a positive effect of health on economic growth, the size of the effect is still subject to intensive debate. We show that, after appropriately controlling for potential spillover effects of population health at the aggregate level, the point estimate of the macroeconomic effect of health is remarkably close to the one found by aggregating the microeconomic effects. Specifically, an increase in the adult survival rate of 10 percentage points is associated with a 9.1 percent increase in labor productivity. This effect is sizable and adds a strong argument for investments in population health over and above the direct welfare benefits of good health.
Keywords: I15; I25; J11; O11; O15; 330; Productivity; Population Health; Micro-Macro Consistency; Human Capital; Economic Development